2016
DOI: 10.56577/sm-2016.462
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary groundwater storage changes from 1950s to present in New Mexico alluvial aquifers using a semi-automated workflow

Abstract: In response to increasing needs to understand the water budget of New Mexico, we have constructed estimates of historical groundwater storage change in the shallow (less than 1000 ft), unconfined alluvial aquifers of the state. Shallow, unconfined alluvial aquifers in New Mexico form the major groundwater reservoirs in many of the urbanized and agricultural areas of the state. This collocation means that alluvial aquifers have been commonly used as a major water source over the last 70 years, possibly leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…It must be viewed with caution because the result is highly dependent on the value for specific yield, which must be assumed in this case. A value of 0.2 was chosen for this study, consistent with previous work (McAda and Barroll, 2002;Rinehart et al, 2016). It is likely that the specific yield varies in space, with depth, and with lithology (e.g., Cederstrand and Becker, 1998).…”
Section: Resultsmentioning
confidence: 98%
“…It must be viewed with caution because the result is highly dependent on the value for specific yield, which must be assumed in this case. A value of 0.2 was chosen for this study, consistent with previous work (McAda and Barroll, 2002;Rinehart et al, 2016). It is likely that the specific yield varies in space, with depth, and with lithology (e.g., Cederstrand and Becker, 1998).…”
Section: Resultsmentioning
confidence: 98%
“…This can be roughly estimated with a few simple calculations. The loss from storage can be estimated first using an intermediate, uniform water-level decline value of 2 feet per year for the period of the 1950s to the 2010s, and a specific yield value of 0.15 (Rinehart et al, 2016) over the total area of surficial and valley-fill deposits in Sunshine Valley (363 km 2 ) (Fig. 4 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the 1950s to the 2010s decades directly, the total loss from storage was 73,487 acre-feet, or an average of 1124 acre-feet/year over 60 years. Rinehart et al (2016) calculated water-level and groundwater-storage changes in alluvial basins of the Rio Grande rift, including the Sunshine Valley region. From the 1950s to the 1990s, Rinehart et al (2016) indicated a similar pattern of variably rising and falling water levels across much of Sunshine Valley, as illustrated in Figure 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where sdtw is the susceptibility based on the median DTW and d is the median DTW. These thresholds were chosen based on observations of normal annual to decadal variations of groundwater levels in basin-fill aquifers across the state observed by Rinehart while conducting a statewide groundwater change analysis (Rinehart et al, 2015(Rinehart et al, , 2016(Rinehart et al, and 2017. Regions with deeper groundwater are more likely to have never flooded and been saturated through the entire thickness.…”
Section: Depth-to-water-based Susceptibilitymentioning
confidence: 99%